Family Decision-Making and Actions in Cancer Emergency Events - Florensius Andri; Eben Haezar Kristian; Stepanus Maman Hermawan (CV. Global Health Science Group, 2025)
Emergency deterioration in cancer patients often occurs unexpectedly at home, requiring families to respond rapidly despite limited knowledge and skills. This study explores the experiences of family caregivers in managing home-based cancer emergencies using a descriptive qualitative approach through in-depth semi-structured interviews with 11 (eleven) family caregivers, analyzed manually with thematic analysis. Four themes emerged. The first theme, Emotional and Psychological Experiences of Families, describes distress such as panic, fear, and confusion that hindered effective responses. The second theme, Family Preparedness and Capabilities in Handling Emergencies, highlights limited knowledge, insufficient practical skills, and the lack of basic equipment, which created uncertainty during initial actions. The third theme, Decision-Making and Family Response Strategies, shows that decisions were made under time pressure and often relied on instinct or brief discussions due to limited guidance. The fourth theme, Social Support and the Healthcare System, emphasizes the importance of communication with health workers and support from neighbors or community volunteers, although delays in accessing emergency services remained common. These findings indicate the need for practical educational programs, clear emergency action guidelines, community-based training, and improved telehealth or hotline services to enhance family preparedness in managing cancer emergencies at home.